Lifecycle Environmental Impact Assessment of an Overtopping Wave Energy Converter Embedded in Breakwater Systems - Patrizi, Nicoletta; Pulselli, Riccardo M.; Neri, Elena; Niccolucci, Valentina; Vicinanza, Diego; Contestabile, Pasquale; Bastianoni, Simone (Frontiers in Energy Research, 2019)
Overtopping breakwater systems are among the most promising technologies for exploiting wave energy to generate electricity. They consist in water reservoirs, embedded in piers, placed on top of ramps, higher than sea-level. Pushed by wave energy, seawater fills up the reservoirs and produces electricity by flowing back down through low headhydro turbines. Different overtopping breakwater systems have been tested worldwide in recent years. This study focuses on the Overtopping BReakwater for Energy Conversion (OBREC) system that has been implemented and tested in the harbor of Naples (Italy). The Life Cycle Assessment of a single replicable module of OBREC has been performed for analyzing potential environmental impacts, in terms of Greenhouse Gas Emissions, considering construction, installation, maintenance, and the operational phases. The Carbon Footprint (i.e., mass of CO2eq) to build wave energy converters integrated in breakwater systems has been estimated, more specifically the “environmental investment” (i.e., the share of Carbon Footprint due to the integration of wave energy converter) needed to generate renewable electricity has been assessed. The Carbon Intensity of Electricity (i.e., the ratio between the CO2eq emitted and the electricity produced) has been then assessed in order to demonstrate the profitability and the opportunity to foster innovation in the field of blue energy. Considering the impact for implementing an operational OBREC module (Carbon Footprint = 1.08 t CO2eq; Environmental Investment = 0.48 t CO2eq) and the electricity production (12.6 MWh/year per module), environmental benefits (avoided emissions) would compensate environmental costs (i.e., Carbon Footprint; Environmental Investment) those provided within a range of 25 and 13 months respectively.